Sex-Related Differences in Shoulder Complex Joint Dynamics Variability During Pediatric Manual Wheelchair Propulsion - Leonardis, Joshua M; Schnorenberg, Alyssa J; Vogel, Lawrence C; Harris, Gerald F; Slavens, Brooke A (Journal of applied biomechanics, 2024)
More than 80% of adult manual wheelchair users with spinal cord injuries will experience shoulder pain. Females and those with decreased shoulder dynamics variability are more likely to experience pain in adulthood. Sex-related differences in shoulder dynamics variability during pediatric manual wheelchair propulsion may influence the lifetime risk of pain. We evaluated the influence of sex on 3-dimensional shoulder complex joint dynamics variability in 25 (12 females and 13 males) pediatric manual wheelchair users with spinal cord injury. Within-subject variability was quantified using the coefficient of variation. Permutation tests evaluated sex-related differences in variability using an adjusted critical alpha of P = .001. No sex-related differences in sternoclavicular or acromioclavicular joint kinematics or glenohumeral joint dynamics variability were observed (all P ≥ .042). Variability in motion, forces, and moments are considered important components of healthy joint function, as reduced variability may increase the likelihood of repetitive strain injury and pain. While further work is needed to generalize our results to other manual wheelchair user populations across the life span, our findings suggest that sex does not influence joint dynamics variability in pediatric manual wheelchair users with spinal cord injury.